2020
DOI: 10.1111/cobi.13459
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of land use and hunting on distributions of tropical mammals

Abstract: Land use and hunting are 2 major pressures on biodiversity in the tropics. Yet, their combined impacts have not been systematically quantified at a large scale. We estimated the effects of both pressures on the distributions of 1884 tropical mammal species by integrating species' range maps, detailed land-use maps (1992 and 2015), species-specific habitat preference data, and a hunting pressure model. We further identified areas where the combined impacts were greatest (hotspots) and least (coolspots) to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 35 publications
3
58
0
Order By: Relevance
“…These results are consistent with previous studies that have reported biodiversity decline and loss within PAs in these regions e.g. Geldmann and others [10], Harrison [69], Laurance and others [70] and Gallego-Zamorano and others [14]. Our findings suggest that the effectiveness of Asian PAs requires urgent attention to improve biodiversity conservation across in continental Asia.…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with previous studies that have reported biodiversity decline and loss within PAs in these regions e.g. Geldmann and others [10], Harrison [69], Laurance and others [70] and Gallego-Zamorano and others [14]. Our findings suggest that the effectiveness of Asian PAs requires urgent attention to improve biodiversity conservation across in continental Asia.…”
Section: Plos Onesupporting
confidence: 93%
“…These threats can have serious conservation and ecological implications. For example, recent assessments of wildlife abundance across tropical forests reported at least 40% decline in mammal distribution range due to hunting [14]. Mammal population declines by 80% and 30% have been reported across tropical forests caused by hunting and land use change respectively [9,15], consequently leading to potential loss of species interaction networks [13,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only studies focusing on TD have assessed the relative impact of multiple threats. In such studies, habitat destruction contributed more than overexploitation to TD declines in tropical mammals and birds, but with wide variation among species (Gallego‐Zamorano et al., 2020; Romero‐Muñoz et al., 2020; Symes et al., 2018), implying that responses into threats may differ between TD and other facets.…”
Section: Discussionmentioning
confidence: 99%
“…However, progress towards achieving the sustainable use of resources globally remains a challenge. Progress towards Aichi target 4.2 on use within safe ecological limits has been assessed as ‘poor’ (Secretariat of the Convention on Biological Diversity 2020) and impacts of hunting is even thought to be increasing (Gallego-Zamorano, Benítez-López et al 2020). Together with land use change, hunting has had negative impacts on species populations, particularly in the tropics where anthropogenic pressure is currently highest and intensifying (Venter, Sanderson et al 2016).…”
Section: Introductionmentioning
confidence: 99%